IMPLEMENTASI RATIONAL EMOTIF BEHAVIORAL THERAPY (REBT) TERHADAP PENGURANGAN TINGKAT KECEMASAN KLIEN “AS” PASCA BENCANA LONGSOR DI DESA MARGAMUKTI KECAMATAN PANGALENGAN KABUPATEN BANDUNG BARAT - Uut Hanafi Rochman (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This study aims to determine the implementation of Rational Emotive Behavior Therapy (REBT) to reduce the level of anxiety experienced by US clients after landslides in Margamukti Pangalengan village. After the landslide, the US client experienced indications of anxiety disorders. Almost everyone experiences an anxiety disorder characterized by anxiety, restlessness that has an impact on emotional, cognitive and physiological disorders caused by past factors. This study uses a quantitative approach with an experimental research design. In this study, the study used a single subject design (SSD) with reselval technique (design with repetition) with the A-B-A model. The results showed that after the implementation of the intervention in the form of REBT therapy, the level of anxiety experienced by US clients experienced anxiety, where at baseline A1, which was in the high category with a score of 22, became the moderate category with a score of 11 in the final phase in the A2 baseline. From these data, it explains that the implementation of REBT therapy affects the reduction of anxiety levels in post-disaster survivors.